2009
DOI: 10.1002/pssc.200881729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stack number on the threshold current density and emission wavelength in quantum dash/dot lasers

Abstract: International audienceInAs quantum dash and dot (QDH and QD) lasers grown by molecular beam epitaxy on InP substrate are studied. The grown lasers with active zone containing multiple stacked layers exhibit lasing wavelength at 1.55 µm. On these devices, the experimental threshold current density reaches its minimum value for a double stacked QDH/QD structure. Other basic laser properties like gain and quantum efficiency are compared. QD lasers exhibit better threshold current densities but equivalent modal ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Semiconductor lasers incorporating quantum confined nanostructures in the active medium has shown superior performances compared to bulk active region lasers [1]- [ 3]. This improvement may be attributed to the availability of discrete energy levels in the conduction and valance bands in these low dimensional structures rather than a continuous band which is the feature of a bulk semiconductor laser.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Semiconductor lasers incorporating quantum confined nanostructures in the active medium has shown superior performances compared to bulk active region lasers [1]- [ 3]. This improvement may be attributed to the availability of discrete energy levels in the conduction and valance bands in these low dimensional structures rather than a continuous band which is the feature of a bulk semiconductor laser.…”
Section: Introductionmentioning
confidence: 99%
“…A typical atomic for microscopy (AFM) images of Qdash and Qdot (Qbox) is shown in Fig. 1(a) and (b), respectively [1]. These structures has got attention recently because of their superior performance than Qfilm and bulk semiconductor lasers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] This may be attributed to the near singular density of state ͑DOS͒, experimental optimization of design/fabrication process parameters, [1][2][3][4][5][6][7][8] and intensive theoretical research. [9][10][11][12][13][14][15] Various numerical techniques have been developed to address the Qdash materials and devices, but mostly concentrating on the energy band and emission characteristics of Qdash structures [10][11][12][13][14] rather than studying the Qdash devices except for a few which looked into Qdash semiconductor optical amplifier ͑SOA͒ 15 and dynamic characteristics of Qdash laser.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Various numerical techniques have been developed to address the Qdash materials and devices, but mostly concentrating on the energy band and emission characteristics of Qdash structures [10][11][12][13][14] rather than studying the Qdash devices except for a few which looked into Qdash semiconductor optical amplifier ͑SOA͒ 15 and dynamic characteristics of Qdash laser. 16 Recently, Tan et al 6 and Zhou et al 7 has experimentally reported that increasing the cavity length result in a redshift of the lasing wavelength from the InAs/InP Qdash lasers which they attribute to the unique DOS of the Qdashes. Inspite of this unusual behavior, no research has been done to confirm this observation theoretically and find out the reason behind it.…”
mentioning
confidence: 99%